Landmarks in Insulin Research - Lawrence, Michael (Frontiers in Endocrinology, 2011)
Ever since the discovery of insulin and its role in the regulation of glucose uptake and utilization, there has been great interest in insulin, its structure and the way in which it interacts with its receptor and effects signal transduction. As the 90th anniversary of the discovery of insulin approaches, it is timely to provide an overview of the landmark discoveries relating to the structure and function of this remarkable molecule and its receptor.